2017
DOI: 10.1105/tpc.16.00577
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stomatal Immunity by Interdependent Functions of a Pathogen-Responsive MPK3/MPK6 Cascade and Abscisic Acid

Abstract: Activation of mitogen-activated protein kinases (MAPKs) is one of the earliest responses after plants sense an invading pathogen. Here, we show that MPK3 and MPK6, two pathogen-responsive MAPKs, and their upstream MAPK kinases, MKK4 and MKK5, are essential to both stomatal and apoplastic immunity. Loss of function of and , or their upstream and , abolishes pathogen/microbe-associated molecular pattern- and pathogen-induced stomatal closure. Gain-of-function activation of MPK3/MPK6 induces stomatal closure inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 96 publications
3
129
0
1
Order By: Relevance
“…MPK3 and MPK6 contribute redundantly to stomatal closure in response to Pto DC3000, which is reversed by COR (8,37,38). We found that Pto DC3000 is able to reopen stomata both in the wild type and hai1 (SI Appendix, Fig.…”
Section: Hai Pp2cs Are Responsible For Aba-mediated Mapk Inactivationmentioning
confidence: 63%
“…MPK3 and MPK6 contribute redundantly to stomatal closure in response to Pto DC3000, which is reversed by COR (8,37,38). We found that Pto DC3000 is able to reopen stomata both in the wild type and hai1 (SI Appendix, Fig.…”
Section: Hai Pp2cs Are Responsible For Aba-mediated Mapk Inactivationmentioning
confidence: 63%
“…EMPIS should have three characteristics: (i) It can mediate ETI signaling even in the absence of the four signaling sectors, (ii) its ETI signaling function is compensated by the four signaling sectors, (iii) its ETI signaling function is inhibited by PTI signaling. However, a recent report of a successful application of engineered MPK3 and 6 (MPK3/6SR) that are chemically inhibitable (Su et al, 2017) could open a route to directly test the hypothesis using quad mpk3 mpk6 MPK6SR plants. Previously, we showed that signaling mediated by MPK3/6 can compensate SA signaling during ETI , which possibly confers characteristics (i) and (ii).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that mutants of the MEKK1–MKK1/MKK2–MPK4 cascade such as mekk1 , mkk1 mkk2 , and mpk4 , all show autoimmune phenotypes and enhanced resistance against Pseudomonas (Suarez‐Rodriguez et al ., ; Gao et al ., ; Qiu et al ., ), while mutants of the MKK4/MKK5–MPK3/MPK6 pathway ( mkk4 mkk5 and mpk3 mpk6 ) show compromised resistance (Su et al ., ). Constitutive activation of MPK3/MPK6 leads to HR‐like cell death and accumulation of defensive phytoalexins (Ren et al ., , ); however, constitutive MPK4 activation compromises both PTI and ETI mediated by the TNL proteins RPS4 and RPP4 (Berriri et al ., ).…”
Section: Summ2 Guards the Mekk1–mkk1/mkk2–mpk4 Cascadementioning
confidence: 97%